Retraction: A simple rhodamine-based dual signalling reversible molecular switch for recognition of Al(iii) with promising applications for advanced logic operations – 'OR', 'Keypad Lock' & 'INHIBIT' logic function and cell-imaging studies. Issue 23 (7th November 2019) - Mistri, Tarun; Alam, Rabiul; Bhowmick, Rahul; Mandal, Sushil Kumar; Dolai, Malay; Khuda-Bukhsh, Anisur Rahman; Ali, Mahammad
Abstract : Retraction of 'A simple rhodamine-based dual signalling reversible molecular switch for recognition of Al(iii ) with promising applications for advanced logic operations – 'OR', 'Keypad Lock' & 'INHIBIT' logic function and cell-imaging studies' by Tarun Mistri et al., Analyst, 2014, DOI: 10.1039/C3AN02255B.